Mycotoxin Exposure and Infant and Young Child Growth in Africa: What Do We Know? - Lombard, Martani J. (Annals of nutrition and metabolism, 2014)
Introduction: Infant and young child (IYC) growth impairment remains a public health problem in Africa partly because infants are exposed to staple foods (contaminated with mycotoxins) at an early age. Understanding the role of mycotoxins in IYC growth is vital, and this paper systematically reviews the available knowledge. Methods: Studies were searched and included if they provided information on African IYC mycotoxin exposure rates and/or growth. Studies were excluded if subjects were older than 15 years, if they were animal studies or focusing on other mycotoxins. Relevant search words were included in search strings. Eight reviews were identified and reference lists scrutinised for additional studies. Results: Ten studies were included; 8 focused on aflatoxin (AF), 2 on fumonisin (FB) and none on deoxynivalenol (DON) and zearalenone (ZEA). AF exposure prevalence reached 100% with levels at 40.4 pg/mg. AF was present in umbilical cords indicating that AF crosses the placenta. Maternal exposure levels were correlated with breast milk levels. The highest levels of serum AF (mean 32.8 pg/mg) were measured in Benin and Togo with 5.4% reaching levels higher than 200 pg/mg. At the end of weaning, children had similar prevalence and exposure levels as adults. Results also indicated that infants with higher levels of maternal exposure had significantly lower height-for-age z-scores (HAZ scores), although there was no significant association between cord AF and infant HAZ scores or AF in cord blood and HAZ scores. Significantly higher mean maternal AF levels related to lower weight-for-age z-scores (WAZ scores) were reported, and infants with higher levels of maternal exposure had significantly lower WAZ scores that decreased over age. Cord AF levels had no effect on infant WAZ scores. One study investigated the association between FB and IYC growth and found that those with FB intakes greater than the provisional maximum tolerable daily intake were significantly shorter (1.3 cm) and lighter (328 g). No studies investigated the role of DON and ZEA. Conclusion: A limited number of epidemiological studies have been conducted, and available research indicates extreme exposures to AF. There are strong associations between AF exposure and stunting and wasting. However, more epidemiological research is urgently needed to understand the role of FB, DON and ZEA in IYC growth.